2020
DOI: 10.1038/s41598-019-56763-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Pandemic Escherichia coli ST131 Plasmidome Proves Restricted Plasmid-clade Associations

Abstract: extraintestinal multidrug resistant Escherichia coli sequence type (ST) 131 is a worldwide pandemic pathogen and a major cause of urinary tract and bloodstream infections. the role of this pandemic lineage in multidrug resistance plasmid dissemination is still scarce. We herein performed a metaanalysis on E. coli ST131 whole-genome sequence (WGS) databases to unravel ST131 plasmidome and specifically to decipher CTX-M encoding plasmids-clade associations. We mined 880 ST131 WGS data and proved that CTX-M-27-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 60 publications
9
42
0
1
Order By: Relevance
“…In these studies and others, the bla CTX-M-27 gene has been associated with fimH30 and fluoroquinolone resistance as part of clade C1-M27. Here, we found the same, as well as noting that the bla CTX-M-27 gene was often embedded in plasmids of pMLST IncF[F1:A2:B20] which was almost exclusively restricted to the C1-M27 clade, as reported by others (Ghosh et al, 2017;Kondratyeva et al, 2020). Interestingly, An IncF[F1:A2:B20] plasmid was also found in a single ST38 strain (URMC_96; Figure 3C).…”
Section: Discussionsupporting
confidence: 89%
“…In these studies and others, the bla CTX-M-27 gene has been associated with fimH30 and fluoroquinolone resistance as part of clade C1-M27. Here, we found the same, as well as noting that the bla CTX-M-27 gene was often embedded in plasmids of pMLST IncF[F1:A2:B20] which was almost exclusively restricted to the C1-M27 clade, as reported by others (Ghosh et al, 2017;Kondratyeva et al, 2020). Interestingly, An IncF[F1:A2:B20] plasmid was also found in a single ST38 strain (URMC_96; Figure 3C).…”
Section: Discussionsupporting
confidence: 89%
“…Using IncF plasmid replicons (FII_1, FIA_2, FIB_20, FII_2, and FIA_1) and a plasmid classification system published recently ( 26 ), we found that group 1 plasmids (combination of FII_1, FIA_2, and FIB_20) were in clades A, B, C1-nonM27, and C1-M27, and group 2 plasmids (combination of FII_2 and FIA_1) were in clades C0 and C2 ( Table 1 ). Group 1 plasmids were common among C1 clades, and group 2 plasmids were common among C2 isolates.…”
Section: Resultsmentioning
confidence: 81%
“…ST131 E. coli strains are of worldwide importance as a quinolone-resistant and ESBL-producing bacteria, the spread of which is attributed to the plasmid. 4 This study shows both the importance of ST410 and that the antimicrobial-resistant pattern of these strains might be different if it spreads. Thus, it is necessary to be aware of the latest epidemiology.…”
Section: Editorial Commentmentioning
confidence: 84%